Earning Management, Firm Size And Its Effect on Tax Aggressiveness With Good Corporate Governance As a Moderating - Dyah Aruning Puspita; Elysabet Ucy Wulandari; Sugeng Hariadi (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Tax aggressiveness is a strategy used by businesses to reduce their tax liabilities. This study is part of a quantitative investigation that looks at how aggressive activities with sound corporate governance, as a moderator, are affected by income management and company size in manufacturing firms and how this affects the IDX in the consumer goods industrial sector. The Indonesia Stock Exchange's official website, https://www.idx.co.id, provides secondary data for this study.Eleven samples listed on the Indonesia Stock Exchange were subjected to multiple linear regression analysis for data analysis in this study. According to the study's findings, tax aggressiveness is significantly impacted by sound corporate governance using an independent commissioner proxy, but it is not significantly impacted by earnings management or firm size. The association between tax aggression and productive management is not moderated by independent commissioners. In the meantime, the company's relationship to tax aggression is moderated by independent commissioners